UHF Metamaterial Absorber with Small-Size Unit Cell by Combining Fractal and Coupling Lines - Shicheng Fan; Yaoliang Song (International Journal of Antennas and Propagation)
We present a perfect UHF metamaterial absorber by combining coupling lines and fractal lines with a very small unit cell. The proposed absorber consists of a surface metal structure and metallic background plane, separated by a dielectric substrate and air. Simulation results show that the absorber has an absorption peak at 442 MHz with 99.73% absorptivity. The ratio between a lattice constant and resonance wavelength is 1/68, significantly less than the existing absorber. The design principle is introduced in detail according to the absorption mechanism of the proposed absorber. Moreover, the absorption peaks remain high with large angles of incidence for both TE and TM polarizations. Due to the small ratio, it can be widely used in radiation suppression for microwave relay communication such as mobile communication and wireless network by changing the parameters of the structure.